Quantitative Proteome Profiling of a S-Nitrosoglutathione Reductase (GSNOR) Null Mutant Reveals a New Class of Enzymes Involved in Nitric Oxide Homeostasis in Plants - Treffon, Patrick; Rossi, Jacopo; Gabellini, Giuseppe; Trost, Paolo; Zaffagnini, Mirko; Vierling, Elizabeth (Frontiers in Plant Science, 2021)
Nitric oxide (NO) is a short-lived radical gas that acts as a signaling molecule in all higher organisms, and that is involved in multiple plant processes, including germination, root growth and fertility. Regulation of NO-levels is predominantly achieved by reaction of reactive nitrogen species (RNS) with glutathione to form S-nitrosoglutathione (GSNO), the principal bioactive form of NO. The enzyme S-nitrosoglutathione reductase (GSNOR) is a major route of NADH-dependent GSNO catabolism and is critical to NO homeostasis. Here, we performed a proteomic analysis examining changes in the total leaf proteome of an Arabidopsis thaliana GSNOR null mutant (hot5-2/gsnor1-3). Significant increases or decreases in proteins associated with chlorophyll metabolism and with redox and stress metabolism provide insight into phenotypes observed in hot5-2/gnsor1-3 plants. Importantly, we identified a significant increase in proteins that belong to the aldo-keto reductase (AKR) protein superfamily, AKR4C8 and 9. Because specific AKRs have been linked to NO metabolism in mammals, we expressed and purified A. thaliana AKR4C8 and 9 and close homologues AKR4C10 and 11 and determined that they have NADPH-dependent activity in GSNO and S-nitroso-coenzyme A (SNO-CoA) reduction. Further, we found an increase of NADPH-dependent GSNO reduction activity in hot5-2/gsnor1-3 mutant plants. These data uncover a new, NADPH-dependent component of NO metabolism that may be integrated with NADH-dependent GSNOR activity to control NO homeostasis in plants.